Evaluation of Business Combination Accounting: Pre and Post PSAK 22 Implementation in PT. Indosat Tbk - Ananda, Emmaculata; Ramadhianti, Najla; Sinulingga, Jentiya (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The primary objective of this research is to scrutinize the application of business combination accounting before and after the implementation of PSAK 22 in Indonesia. Employing quantitative descriptive methods and purposive sampling techniques, the study draws on secondary data, specifically the financial statements of PT. Indosat Tbk on the Indonesia Stock Exchange spanning from 2009 to 2012. Before the adoption of PSAK 22, PT. Indosat Tbk employed the purchase method in business combination transactions, recognizing and amortizing goodwill in accordance with relevant standards. Post-PSAK 22 implementation, the company switched to the acquisition method for recording business combination transactions. Financial performance is assessed through profitability ratio analysis. The findings indicate that after the application of PSAK 22, PT. Indosat Tbk's financial performance did not exhibit improvement compared to the pre-PSAK 22 period. The implication of these results suggests that the transition to PSAK 22 might not have yielded the anticipated positive impact on the company's financial standing. This insight can be valuable for companies navigating similar accounting transitions, emphasizing the need for careful consideration and evaluation of the implications of accounting standard changes on overall financial performance.